Minimization of Soil and Nutrient Losses in Maize-Based Cropping Systems in the Mid-Hills of Central Nepal - Atreya, K.; Sharma, S.; Bajracharya, R.M. (Kathmandu University Journal of Science, Engineering and Technology, 2005)
Soil nutrient depletion is a major concern in terms of resource utilization and optimization of production in the middle hills of Nepal. Soil and nutrient losses from agricultural land is responsible for pollution of surface waters and this reduces the productive capacity of land. A field experiment was initiated in May 2001 on acidic sandy loam soil in Kavre district; Nepal to investigate the efficiency of widely recommended researchable options for soil conservation. The experimental plots were set up as a two factorial design with three main factors (mulching, reduced tillage and conventional farmers' practice as control) and were divided on the basis of cropping patterns (maize sole and maize inter-cropped with soybean). Soil N, P, K, and OM losses were determined from soil eroded in runoff. Nutrient loss in pre- monsoon period (in the month of May) was highly significant among the management practices. Much of nutrient (60 to 90 percent of annual) losses occurred during this period. As compared to conventional farmers' practice, mulching reduced annual soil organic matter loss by 52 percent, annual total nitrogen by 46 percent, annual available P2O5 by 32 percent and annual exchangeable K2O by 53 percent in maize – mustard cropping system. Similarly, in maize + soybean - mustard cropping system, the annual loss of these nutrients were reduced by 58, 49, 26 and 60 percent, respectively. Reduced tillage, on the other hand, produced higher soil loss and hence more nutrient and organic matter loss as compared to mulching practice because of freshly prepared plots and hence less vegetation and more compaction.